Collaborative research writing as mentoring in a U.S. English doctoral program - Bommarito, Daniel V. (Journal of Writing Research, 2016)
This qualitative study investigates an approach to mentoring that offers guided practice in authentic disciplinary activities prior to the dissertation stage. The mentoring project under investigation was unique in that it was designed to double as an authentic collaborative research study and as an opportunity for professional development. Starting from the assumption that writing is a function of the activities that underlie it, this article examines the embedded practices out of which writing emerges—namely, the forms of participation taken up by the doctoral student participants during their research and writing, as well as the mentoring practices enacted alongside. Findings show that participants devoted considerable attention to negotiating individual roles and responsibilities throughout the project and to negotiating emerging research objectives in response to a variety of unexpected obstacles posed by the research environment. Additionally, participants encountered significant difficulties constructing claims in the collaborative setting, owing in part to their status as disciplinary newcomers. Findings also show that the design of the collaborative project helped facilitate and distribute mentoring across the diverse research team in productive ways.